The logistics warehouse and urban financialization: from production flexibility to real estate - Yassu, Alexandre Mitsuro da Silveira (Pontifícia Universidade Católica de São Paulo, 2021)
Amid transformations in the (re)production of the metropolis caused by production and real estate restructuring, the logistics warehouse emerges as an expression of both: it is part of the changes in the organization of the capitalist company and it is a new real estate product aligned with the demand for large retailers and digital commerce, involving financial and real estate agents on multiple scales, from local to global. This phenomenon has invaded the city of Cajamar and transformed it into the main logistics hub of the Metropolitan Region of São Paulo. Based on the case of Cajamar, our objective is to explore the genesis of this new real estate commodity, its specific forms of ownership and circulation, its modeling as a product and its form of insertion in space.